High-toughness asphalt based on sbs-epoxy grafting crosslinking and preparation method thereof

CN122878770APending Publication Date: 2026-10-09JIANGSU ZENGGUANG COMPOSITE MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611086368.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

随着交通荷载不断重型化、交通量持续增长以及极端气候条件频发,传统基质沥青已难以满足路面材料对高温抗车辙、低温抗裂及耐久性的综合性能要求

Benefits of technology

双端环氧基SBS的两个端环氧基均可与双酚A型环氧树脂中的环氧基团发生反应,使SBS分子链两端均以化学键锚固在双酚A型环氧树脂网络中,提高了双端基SBS在交联网络中的“桥连”作用,显著提升了SBS弹性体网络与双酚A型环氧树脂刚性网络之间的界面结合强度,且双端环氧基SBS参与接枝交联后,可形成SBS分子链“贯穿”双酚A型环氧树脂交联网络的拓扑结构,应力在材料中的传递和分散更为均匀,有利于同时提升高温抗车辙能力和低温抗裂能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a high-toughness asphalt based on SBS-epoxy grafting crosslinking and a preparation method thereof, and relates to the technical field of asphalt; the high-toughness asphalt comprises the following raw materials in parts by weight: 100-120 parts of base asphalt, 6-10 parts of double-end epoxy-based SBS, 2-5 parts of epoxy resin, 1-3 parts of a curing agent, 0.4-0.8 parts of a crosslinking promoter, 1-3 parts of a compatibilizer and 0.1-0.5 parts of a stabilizer; the application has the effect of improving the high-temperature rutting resistance and low-temperature cracking resistance of the asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of asphalt technology, and in particular to a high-toughness asphalt based on SBS-epoxy graft crosslinking and its preparation method. Background Technology

[0002] Asphalt is the most widely used pavement material in road engineering, and its performance directly affects the service life of the pavement and driving safety. With the increasing weight of traffic loads, the continuous growth of traffic volume, and the frequent occurrence of extreme weather conditions, traditional base asphalt can no longer meet the comprehensive performance requirements of pavement materials for high-temperature rutting resistance, low-temperature crack resistance, and durability.

[0003] In traditional physically blended SBS-modified asphalt, SBS and asphalt are simply physically entangled with weak interfacial bonding. At high temperatures, the SBS network is prone to loosening and deformation, leading to rutting and shoving of the road surface; at low temperatures, the asphalt matrix becomes brittle, and the interface between the SBS elastomer and the asphalt phase easily becomes a stress concentration point, triggering low-temperature shrinkage cracking and reflective cracking. Summary of the Invention

[0004] To improve the high-temperature rutting resistance and low-temperature crack resistance of asphalt, this application provides a high-toughness asphalt based on SBS-epoxy graft crosslinking and its preparation method.

[0005] Firstly, this application provides a high-toughness asphalt based on SBS-epoxy graft crosslinking, which adopts the following technical solution: A high-toughness asphalt based on SBS-epoxy graft crosslinking comprises the following raw materials in parts by weight: 100-120 parts of base asphalt, 6-10 parts of SBS with double-ended epoxy groups, 2-5 parts of bisphenol A type epoxy resin, 1-3 parts of curing agent, 0.4-0.8 parts of crosslinking accelerator, 1-3 parts of compatibilizer, and 0.1-0.5 parts of stabilizer.

[0006] By adopting the above technical solution, both terminal epoxy groups of the dual-epoxy group SBS can react with the epoxy groups in the bisphenol A type epoxy resin, so that both ends of the SBS molecular chain are chemically anchored in the bisphenol A type epoxy resin network. This improves the "bridging" effect of the dual-epoxy group SBS in the cross-linking network, significantly enhances the interfacial bonding strength between the SBS elastomer network and the bisphenol A type epoxy resin rigid network, and after the dual-epoxy group SBS participates in graft cross-linking, it can form a topological structure in which the SBS molecular chain "penetrates" the bisphenol A type epoxy resin cross-linking network. The stress transmission and dispersion in the material are more uniform, which is beneficial to simultaneously improve the high-temperature rutting resistance and low-temperature crack resistance.

[0007] Preferably, the method for preparing the di-epoxy group-terminated SBS includes the following steps: S1. Under nitrogen protection, cyclohexane, styrene, and tetrahydrofuran are mixed, heated and stirred, then n-butyllithium is added. After the reaction is complete, butadiene is introduced to continue the reaction and form a polystyrene-polybutadiene diblock active chain. S2. Ethylene oxide is added to the reaction system. After the reaction is complete, epichlorohydrin is added. After the reaction is complete, a single-terminated epoxy group SBS active chain is generated. Epichlorohydrin is then added to the reaction system as a coupling agent. After the reaction is complete, a double-terminated epoxy group SBS crude product is formed. S3. The reaction was terminated by adding methanol and an antioxidant. After devolatilization, drying and granulation, the double-terminated epoxy group SBS was obtained.

[0008] By adopting the above technical solution and using the "active anionic polymerization-end group conversion-coupling" process, epoxy groups are introduced at both ends of the SBS molecular chain. This not only does not destroy the carbon-carbon double bond structure of the polybutadiene segment in the SBS main chain and preserves the original elasticity and flexibility of SBS to the greatest extent, but also ensures that efficient "double anchoring" chemical crosslinking points can be formed in the subsequent asphalt modification.

[0009] Furthermore, the two terminal epoxy groups of the bi-epoxy group SBS undergo ring-opening chemical reactions with the epoxy groups in the bisphenol A type epoxy resin, forming a closed-loop structure of "epoxy resin rigid network - SBS elastomer bridging segment - epoxy resin rigid network". This "chemical bridging" effect means that SBS is no longer an isolated "island" physically dispersed in the epoxy resin, but rather part of a cross-linked network, significantly improving the interfacial bonding strength, so that the bi-epoxy group SBS prepared in this invention can be applied to high-toughness asphalt.

[0010] Preferably, the bisphenol A type epoxy resin is prepared by modification, and the method for preparing the modified bisphenol A type epoxy resin includes the following steps: P1. Nanomaterials are added to toluene, ultrasonically dispersed, and then silane coupling agent and triethylamine are added. The reaction occurs under nitrogen protection. After the reaction is completed, the nanomaterials with surface-grafted epoxy groups are obtained by separation, washing and drying. P2. After mixing the nanomaterial with epoxy groups grafted on the surface in step P1 with bisphenol A type epoxy resin, toluene, and hydroquinone, the mixture is ultrasonically dispersed and then fully reacted under nitrogen protection. After the reaction is completed, the mixture is distilled under reduced pressure to obtain modified bisphenol A type epoxy resin.

[0011] By adopting the above technical solution, bisphenol A epoxy resin, after curing, has a high crosslinking density and high molecular chain rigidity, making it essentially a brittle material. Asphalt pavements need to withstand dynamic loads and low-temperature shrinkage; therefore, a silane coupling agent is used as a "molecular bridge" to graft nanomaterials onto the bisphenol A epoxy resin molecular chain via chemical bonds, forming a "nanoparticle-epoxy resin" chemically bonded structure.

[0012] On the one hand, this chemical bonding structure significantly enhances the interfacial bonding strength between nanoparticles and the resin matrix, preventing nanoparticle aggregation. Moreover, this "rigid particle toughening" mechanism gives the cured cyclobisphenol A epoxy resin phase better crack resistance, avoiding overall pavement damage caused by the brittleness of the epoxy phase itself. On the other hand, when this nanomaterial grafted with bisphenol A epoxy resin is used in combination with SBS with double-ended epoxy groups for asphalt modification, the epoxy groups on the surface of the nanoparticles and the grafted epoxy resin segments can both participate in the construction of the SBS-epoxy graft crosslinking network, forming a "nanomaterial-epoxy resin-SBS" ternary chemical bonding network, further improving the high-temperature rutting resistance and low-temperature crack resistance of the modified asphalt.

[0013] Preferably, the mass ratio of the nanomaterial to the bisphenol A epoxy resin is (6-13):100.

[0014] By adopting the above technical solution and controlling the mass ratio of nanomaterials and bisphenol A epoxy resin within the above range, the high-temperature rutting resistance and low-temperature crack resistance of asphalt can be effectively improved.

[0015] Preferably, the nanomaterials include nano-silica and nano-cellulose whiskers, wherein the mass ratio of nano-silica to nano-cellulose whiskers is (2-5):1.

[0016] By employing the above technical solution, the silane coupling agent acts as a "molecular bridge," simultaneously achieving surface epoxy functionalization of both nano-silica and nano-cellulose whiskers. The methoxy group at one end of the silane coupling agent reacts with the silanol groups of nano-silica and the hydroxyl groups of CNC, introducing epoxypropyl groups into the surface of both nanoparticles. Under the action of a catalyst, these epoxypropyl groups react with the secondary hydroxyl groups in the bisphenol A type epoxy resin molecular chain to form Si-OC bonds or CNC-OC bonds, thereby simultaneously grafting both nanoparticles onto the epoxy resin molecular chain through chemical bonds.

[0017] Spherical nano-SiO2 and rod-shaped nano-cellulose whiskers are uniformly dispersed in an epoxy resin matrix through chemical bonds, forming a "sphere-rod" dual-nano synergistic reinforcement structure. The rigid spherical structure of nano-silica provides modulus support and compressive strength, while the high aspect ratio structure of nano-cellulose whiskers provides stress transfer and crack deflection toughening functions. The synergistic effect of the two achieves a dual-effect "reinforcement-toughening" of the epoxy resin.

[0018] Preferably, the curing agent is a latent curing agent for polyurea wall material microcapsules, the core material of the latent curing agent for polyurea wall material microcapsules is triethylenetetramine, and the wall material of the latent curing agent for polyurea wall material microcapsules includes toluene diisocyanate and diethylenetriamine.

[0019] By employing the above technical solution, the polar groups on the polyurea capsule wall molecular structure can form hydrogen bonds with the hydroxyl and epoxy groups on the epoxy resin molecular chain, enhancing the interfacial bonding force between the microcapsules and the epoxy resin matrix. During the curing process, after the microcapsules rupture and release the curing agent, the polyurea capsule wall fragments remain in the cross-linked network, which can act as an organic rigid filler, playing a role in stress dispersion and micro-area toughening.

[0020] Preferably, the preparation method of the latent curing agent for the polyurea wall material microcapsules includes the following steps: S10. Triethylenetetramine is added to ethyl acetate and stirred until homogeneous to obtain a triethylenetetramine solution. Toluene diisocyanate is then added and stirred thoroughly to obtain an oil phase. Tween-80 and diethylenetriamine are added to deionized water and stirred until homogeneous. The pH is adjusted to 8-10 with a pH adjuster to obtain an aqueous phase. S20. The oil phase is added to the aqueous phase to form an oil-in-water emulsion. Under nitrogen protection, the emulsion is allowed to react fully. After the reaction is complete, the emulsion is separated, washed, and dried to obtain a latent curing agent for polyurea wall material microcapsules.

[0021] By employing the above technical solution, the epoxy groups at both ends of the double-ended epoxy molecular chain can react with the active hydrogen in the amino groups or urea bonds on the surface of the polyurea capsule wall to form chemical bonds. This chemical grafting reaction can establish a covalent connection between the microcapsule and the SBS molecular chain, "anchoring" the microcapsule in the SBS elastomer network. This can inhibit the migration and aggregation of microcapsules in the asphalt melt, and also allow the SBS elastomer network to absorb impact energy after the microcapsule ruptures, avoiding localized stress concentration caused by capsule wall rupture.

[0022] Modified bisphenol A epoxy resin possesses abundant surface polar groups and a high specific surface area. The polar groups in the microencapsulated polyurea wall material can form a hydrogen bond network with the silanol and cellulose hydroxyl groups on the surface of the dual nanoparticles, enhancing the dispersion uniformity and interfacial bonding strength of the microcapsules in the modified epoxy resin matrix.

[0023] When the microcapsules rupture during the construction and compaction process, the released curing agent core material can not only catalyze the cross-linking and curing reaction of epoxy resin, but also react with the unreacted epoxy groups on the molecular chain of the double nano-grafted modified epoxy resin, further promoting the anchoring of the double nanoparticles in the curing network through chemical bonds, and improving the construction of the "nano SiO2-nano CNC-epoxy resin-SBS" quaternary cross-linking network.

[0024] Preferably, the mass ratio of the core material to the wall material is 1:(0.6-0.8).

[0025] By adopting the above technical solution and controlling the mass ratio of core material to wall material within the above range, the toughening effect of adding latent curing agent of polyurea wall material microcapsule to the system can be effectively improved.

[0026] Preferably, the crosslinking promoter is one of 2-methylimidazole, triethylamine or benzyldimethylamine, the compatibilizer is one of SBS-g-MAH or epoxidized soybean oil, and the stabilizer is one of sulfur or dicumyl peroxide.

[0027] Secondly, this application provides a method for preparing high-toughness asphalt based on SBS-epoxy graft crosslinking as described in the first aspect, employing the following technical solution. A method for preparing high-toughness asphalt based on SBS-epoxy graft crosslinking includes the following steps: S100. After heating the base asphalt, add double-ended epoxy group SBS, compatibilizer and stabilizer, stir evenly to obtain a pre-dispersion; S200: Add bisphenol A type epoxy resin and crosslinking accelerator to the pre-dispersion and stir evenly; then add curing agent, stir thoroughly, and cure to obtain high-toughness asphalt.

[0028] In summary, this application includes at least one of the following beneficial technical effects: Both terminal epoxy groups of the dual-epoxy group SBS can react with the epoxy groups in the bisphenol A type epoxy resin, anchoring both ends of the SBS molecular chain to the bisphenol A type epoxy resin network by chemical bonds. This enhances the "bridging" effect of the dual-epoxy group SBS in the cross-linking network, significantly improving the interfacial bonding strength between the SBS elastomer network and the bisphenol A type epoxy resin rigid network. Furthermore, after the dual-epoxy group SBS participates in graft cross-linking, it can form a topological structure in which the SBS molecular chain "penetrates" the bisphenol A type epoxy resin cross-linking network, resulting in more uniform stress transmission and dispersion in the material. This is beneficial for simultaneously improving high-temperature rutting resistance and low-temperature crack resistance.

[0029] By using silane coupling agents as "molecular bridges," nanomaterials are chemically grafted onto the molecular chains of bisphenol A epoxy resin, forming a "nanoparticle-epoxy resin" chemical bond structure. On the one hand, this chemical bond structure significantly enhances the interfacial bonding strength between the nanoparticles and the resin matrix, preventing nanoparticle aggregation. Moreover, this "rigid particle toughening" mechanism gives the cured cyclobisphenol A epoxy resin phase better crack resistance, preventing overall pavement damage caused by the brittleness of the epoxy phase itself. On the other hand, when this nanomaterial-grafted bisphenol A epoxy resin is used in conjunction with double-terminated epoxy group SBS for asphalt modification, the epoxy groups on the surface of the nanoparticles and the grafted epoxy resin segments can both participate in the construction of the SBS-epoxy graft crosslinking network, forming a "nanoparticle-epoxy resin-SBS" ternary chemical bond network, further improving the high-temperature rutting resistance and low-temperature crack resistance of the modified asphalt. Detailed Implementation

[0030] Unless otherwise specified, all raw materials used in this application are available from commercially available sources. The following detailed description of this application is provided in conjunction with specific examples: Raw material specifications: Bisphenol A type epoxy resin (CAS No.: 25085-99-8) is provided by Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.; nano silica (CAS No.: 7631-86-9) is provided by Shanghai Maclean Biochemical Technology Co., Ltd.; nano cellulose whiskers are provided by Shenzhen Huano Biotechnology Co., Ltd.; triethylenetetramine (CAS No.: 112-24-3) is provided by Shandong Jinyueyuan New Material Co., Ltd.; toluene diisocyanate (CAS No.: 26471-62-5) is provided by Guangzhou Northern Chemical Co., Ltd.; diethylenetriamine (CAS No.: 111-40-0) is provided by Jinan Liyang Chemical Co., Ltd.; and the product number of SBS-g-MAH (CAS No.: 88497-56-7) is 5541254. Example

[0031] The high-toughness asphalt comprises the following raw materials by weight: 110g base asphalt, 8g double-terminated epoxy SBS, 4g bisphenol A type epoxy resin, 2g curing agent, 0.6g crosslinking accelerator, 2g compatibilizer, and 0.3g stabilizer.

[0032] The preparation method of SBS with di-terminated epoxy groups includes the following steps: S1. Under nitrogen protection, mix 500g cyclohexane, 35g styrene and 1g tetrahydrofuran, start stirring, heat to 50℃, add 1g n-butyllithium, react for 40 minutes, then introduce 65g butadiene, control the reaction temperature at 60℃, and continue to react for 50 minutes to form a polystyrene-polybutadiene diblock active chain. S2. Add 1g of ethylene oxide to the reaction system and react at 55℃ for 10 minutes. Add 2g of epichlorohydrin, raise the temperature to 65℃, and react for 20 minutes to generate single-terminated epoxy group SBS active chain. Add another 1.2g of epichlorohydrin as a coupling agent to the reaction system and continue to react at 65℃ for 60 minutes to form double-terminated epoxy group SBS crude product. S3. Add 0.8 parts of methanol to the reaction system, stir for 15 minutes, terminate the reaction, and add 0.2g of antioxidant 1076 and 0.2g of antioxidant 168. After devolatilization, centrifugal dehydration, separation by vibrating screen, hot air drying (temperature 85℃, time 2 hours), and finally granulation, the double-terminated epoxy group SBS is obtained.

[0033] The curing agent is a latent curing agent for polyurea wall material microcapsules. The preparation method of the latent curing agent for polyurea wall material microcapsules includes the following steps: S10. After cooling 100g of triethylenetetramine in an ice-water bath at 0-5℃, add it to 300g of ethyl acetate and stir until completely dissolved to obtain a triethylenetetramine solution. Then add 50g of toluene diisocyanate and stir at 0-5℃ for 30 seconds to obtain an oil phase. Add 5g of Tween-80 and 20g of diethylenetriamine to 450g of deionized water, add 0.5g of polyvinyl alcohol as a protective colloid, and adjust the pH to 9 with a pH adjuster (10% sodium hydroxide solution) to obtain an aqueous phase. S20. Under high-speed shear dispersion conditions (shear speed of 8000 rpm and shear time of 20 min), the oil phase is added to the aqueous phase to form an oil-in-water emulsion. The emulsion is then transferred to a reaction vessel, heated to 50°C under nitrogen protection, and stirred for 5 h. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, and the precipitate is washed three times alternately with deionized water and anhydrous ethanol. The precipitate is then vacuum dried at 50°C for 18 h to obtain a latent curing agent for polyurea wall material microcapsules.

[0034] The crosslinking agent is 2-methylimidazole, the compatibilizer is SBS-g-MAH, and the stabilizer is sulfur.

[0035] The preparation method of high-toughness asphalt includes the following steps: S100. Heat the base asphalt to 180°C, add double-terminated epoxy SBS, compatibilizer and stabilizer, and stir at 500 rpm for 40 min to obtain a pre-dispersion. S200: Add bisphenol A type epoxy resin and crosslinking accelerator to the pre-dispersion, heat to 170℃, and shear at 3000rpm for 30 minutes; then cool to 140℃, add polyurea wall material microcapsule latent curing agent, stir at 500rpm for 20 minutes to ensure uniform mixing of all components, and finally keep warm and cure at 135℃ for 2 hours to obtain high-toughness asphalt. Example

[0036] The high-toughness asphalt comprises the following raw materials by weight: 100g base asphalt, 6g SBS with double-ended epoxy groups, 2g bisphenol A type epoxy resin, 1g curing agent, 0.4g crosslinking accelerator, 1g compatibilizer, and 0.1g stabilizer.

[0037] The preparation method of SBS with di-terminated epoxy groups includes the following steps: S1. Under nitrogen protection, mix 500g cyclohexane, 35g styrene and 1g tetrahydrofuran, start stirring, heat to 50℃, add 1g n-butyllithium, react for 40 minutes, then introduce 65g butadiene, control the reaction temperature at 60℃, and continue to react for 50 minutes to form a polystyrene-polybutadiene diblock active chain. S2. Add 1g of ethylene oxide to the reaction system and react at 55℃ for 10 minutes. Add 2g of epichlorohydrin, raise the temperature to 65℃, and react for 20 minutes to generate single-terminated epoxy group SBS active chain. Add another 1.2g of epichlorohydrin as a coupling agent to the reaction system and continue to react at 65℃ for 60 minutes to form double-terminated epoxy group SBS crude product. S3. Add 0.8 parts of methanol to the reaction system, stir for 15 minutes, terminate the reaction, and add 0.2g of antioxidant 1076 and 0.2g of antioxidant 168. After devolatilization, centrifugal dehydration, separation by vibrating screen, hot air drying (temperature 85℃, time 2 hours), and finally granulation, the double-terminated epoxy group SBS is obtained.

[0038] The curing agent is a latent curing agent for polyurea wall material microcapsules. The preparation method of the latent curing agent for polyurea wall material microcapsules includes the following steps: S10. After cooling 100g of triethylenetetramine in an ice-water bath at 0-5℃, add it to 300g of ethyl acetate and stir until completely dissolved to obtain a triethylenetetramine solution. Then add 40g of toluene diisocyanate and stir at 0-5℃ for 30 seconds to obtain an oil phase. Add 5g of Tween-80 and 20g of diethylenetriamine to 450g of deionized water, add 0.5g of polyvinyl alcohol as a protective colloid, and adjust the pH to 9 with a pH adjuster (10% sodium hydroxide solution) to obtain an aqueous phase. S20. Under high-speed shear dispersion conditions (shear speed of 8000 rpm and shear time of 20 min), the oil phase is added to the aqueous phase to form an oil-in-water emulsion. The emulsion is then transferred to a reaction vessel, heated to 50°C under nitrogen protection, and stirred for 5 h. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, and the precipitate is washed three times alternately with deionized water and anhydrous ethanol. The precipitate is then vacuum dried at 50°C for 18 h to obtain a latent curing agent for polyurea wall material microcapsules.

[0039] The cross-linking accelerator is triethylamine, the compatibilizer is epoxidized soybean oil, and the stabilizer is dicumyl peroxide.

[0040] The preparation method of high-toughness asphalt includes the following steps: S100. Heat the base asphalt to 180°C, add double-terminated epoxy SBS, compatibilizer and stabilizer, and stir at 500 rpm for 40 min to obtain a pre-dispersion. S200. Add bisphenol A type epoxy resin and crosslinking accelerator to the pre-dispersion, heat to 170℃, and shear at 3000rpm for 30 minutes; then cool to 140℃, add polyurea wall material microcapsule latent curing agent, stir at 500rpm for 20 minutes to make the components uniformly mixed, and finally keep warm and cure at 135℃ for 2 hours to obtain high toughness asphalt. Example

[0041] The high-toughness asphalt comprises the following raw materials by weight: 120g base asphalt, 10g double-terminated epoxy SBS, 5g bisphenol A type epoxy resin, 3g curing agent, 0.8g crosslinking accelerator, 3g compatibilizer, and 0.5g stabilizer.

[0042] The preparation method of SBS with di-terminated epoxy groups includes the following steps: S1. Under nitrogen protection, mix 500g cyclohexane, 35g styrene and 1g tetrahydrofuran, start stirring, heat to 50℃, add 1g n-butyllithium, react for 40 minutes, then introduce 65g butadiene, control the reaction temperature at 60℃, and continue to react for 50 minutes to form a polystyrene-polybutadiene diblock active chain. S2. Add 1g of ethylene oxide to the reaction system and react at 55℃ for 10 minutes. Add 2g of epichlorohydrin, raise the temperature to 65℃, and react for 20 minutes to generate single-terminated epoxy group SBS active chain. Add another 1.2g of epichlorohydrin as a coupling agent to the reaction system and continue to react at 65℃ for 60 minutes to form double-terminated epoxy group SBS crude product. S3. Add 0.8 parts of methanol to the reaction system, stir for 15 minutes, terminate the reaction, and add 0.2g of antioxidant 1076 and 0.2g of antioxidant 168. After devolatilization, centrifugal dehydration, separation by vibrating screen, hot air drying (temperature 85℃, time 2 hours), and finally granulation, the double-terminated epoxy group SBS is obtained.

[0043] The curing agent is a latent curing agent for polyurea wall material microcapsules. The preparation method of the latent curing agent for polyurea wall material microcapsules includes the following steps: S10. After cooling 100g of triethylenetetramine in an ice-water bath at 0-5℃, add it to 300g of ethyl acetate and stir until completely dissolved to obtain a triethylenetetramine solution. Then add 60g of toluene diisocyanate and stir at 0-5℃ for 30 seconds to obtain an oil phase. Add 5g of Tween-80 and 20g of diethylenetriamine to 450g of deionized water, add 0.5g of polyvinyl alcohol as a protective colloid, and adjust the pH to 9 with a pH adjuster (10% sodium hydroxide solution) to obtain an aqueous phase. S20. Under high-speed shear dispersion conditions (shear speed of 8000 rpm and shear time of 20 min), the oil phase is added to the aqueous phase to form an oil-in-water emulsion. The emulsion is then transferred to a reaction vessel, heated to 50°C under nitrogen protection, and stirred for 5 h. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, and the precipitate is washed three times alternately with deionized water and anhydrous ethanol. The precipitate is then vacuum dried at 50°C for 18 h to obtain a latent curing agent for polyurea wall material microcapsules.

[0044] The crosslinking agent is benzyl dimethylamine, the compatibilizer is SBS-g-MAH, and the stabilizer is sulfur.

[0045] The preparation method of high-toughness asphalt includes the following steps: S100. Heat the base asphalt to 180°C, add double-terminated epoxy group SBS, compatibilizer and stabilizer, and stir at 500 rpm for 40 min to obtain a pre-dispersion. S200. Add bisphenol A type epoxy resin and crosslinking accelerator to the pre-dispersion, heat to 170℃, and shear at 3000rpm for 30 minutes; then cool to 140℃, add polyurea wall material microcapsule latent curing agent, stir at 500rpm for 20 minutes to make the components uniformly mixed, and finally keep warm and cure at 135℃ for 2 hours to obtain high toughness asphalt. Example

[0046] The difference between Example 4 and Example 1 is that the mass ratio of core material to wall material is 1:0.5, the core material is triethylenetetramine, and the wall material includes toluene diisocyanate and diethylenetriamine. Example

[0047] The difference between Example 5 and Example 1 is that the mass ratio of core material to wall material is 1:0.9, the core material is triethylenetetramine, and the wall material includes toluene diisocyanate and diethylenetriamine. Example

[0048] The difference between Example 6 and Example 1 is that the bisphenol A type epoxy resin is modified to obtain the bisphenol A type epoxy resin. The preparation method of the bisphenol A type epoxy resin includes the following steps. P1. Add 10g of nanomaterial to 200g of toluene, disperse ultrasonically for 30min, then add 4g of KH-560 and 0.6g of triethylamine, heat to 80℃ under nitrogen protection, stir and reflux for 6h. After the reaction is completed, centrifuge, wash 3 times with anhydrous ethanol, and vacuum dry at 80℃ for 12h to obtain nanomaterial with surface-grafted epoxy groups. P2. The nanomaterial with epoxy groups grafted on the surface in step P1 was mixed with 100g of bisphenol A type epoxy resin, 200g of toluene, and 0.04g of hydroquinone. The mixture was ultrasonically dispersed for 20min. Under nitrogen protection, the temperature was raised to 120℃ and stirred and refluxed for 6h. After the reaction was completed, toluene was removed by vacuum distillation (80℃, -0.095MPa, 2h) to obtain the modified epoxy resin.

[0049] The nanomaterials include nano-silica and nano-cellulose whiskers, with a mass ratio of 3.5:1. Example

[0050] The difference between Example 7 and Example 1 is that the bisphenol A type epoxy resin was modified to obtain the bisphenol A type epoxy resin. The preparation method of the bisphenol A type epoxy resin includes the following steps. P1. Add 6g of nanomaterial to 200g of toluene, disperse ultrasonically for 30min, then add 4g of KH-560 and 0.6g of triethylamine, heat to 80℃ under nitrogen protection, stir and reflux for 6h. After the reaction is completed, centrifuge, wash 3 times with anhydrous ethanol, and vacuum dry at 80℃ for 12h to obtain nanomaterial with surface-grafted epoxy groups. P2. The nanomaterial with epoxy groups grafted on the surface in step P1 was mixed with 100g of bisphenol A type epoxy resin, 200g of toluene, and 0.04g of hydroquinone. The mixture was ultrasonically dispersed for 20min. Under nitrogen protection, the temperature was raised to 120℃ and stirred and refluxed for 6h. After the reaction was completed, toluene was removed by vacuum distillation (80℃, -0.095MPa, 2h) to obtain the modified epoxy resin.

[0051] The nanomaterials include nano-silica and nano-cellulose whiskers, with a mass ratio of 2:1. Example

[0052] The difference between Example 8 and Example 1 is that the bisphenol A type epoxy resin was modified to obtain the bisphenol A type epoxy resin. The preparation method of the bisphenol A type epoxy resin includes the following steps. P1. Add 13g of nanomaterial to 200g of toluene, disperse ultrasonically for 30min, then add 4g of KH-560 and 0.6g of triethylamine, heat to 80℃ under nitrogen protection, stir and reflux for 6h. After the reaction is completed, centrifuge, wash 3 times with anhydrous ethanol, and vacuum dry at 80℃ for 12h to obtain nanomaterial with surface-grafted epoxy groups. P2. The nanomaterial with epoxy groups grafted on the surface in step P1 was mixed with 100g of bisphenol A type epoxy resin, 200g of toluene, and 0.04g of hydroquinone. The mixture was ultrasonically dispersed for 20min. Under nitrogen protection, the temperature was raised to 120℃ and stirred and refluxed for 6h. After the reaction was completed, toluene was removed by vacuum distillation (80℃, -0.095MPa, 2h) to obtain the modified epoxy resin.

[0053] The nanomaterials include nano-silica and nano-cellulose whiskers, with a mass ratio of 5:1. Example

[0054] The difference between Example 9 and Example 7 is that the mass ratio of nano-silica to nano-cellulose whiskers is 1:1. Example

[0055] The difference between Example 10 and Example 7 is that the mass ratio of nano-silica to nano-cellulose whiskers is 6:1.

[0056] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the di-epoxy group SBS is replaced with ordinary unmodified SBS.

[0057] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the fixative is an unmicroencapsulated liquid triethylenetetramine curing agent.

[0058] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 does not contain SBS with two-terminal epoxy groups.

[0059] Comparative Example 4 The difference between Comparative Example 4 and Example 6 is that the nanomaterial is nano-silica.

[0060] Comparative Example 5 The difference between Comparative Example 5 and Example 6 is that the nanofiller is nanocellulose whiskers.

[0061] Performance testing: The following performance tests were performed on the samples of Examples 1-10 and Comparative Examples 1-5: 1. High-temperature rutting resistance Using GB / T4507 "Determination of Softening Point of Asphalt" as the testing reference, the softening point of the samples was tested. Each sample was tested 3 times, and the average value was taken. The test results were recorded in Table 1.

[0062] 2. Low-temperature crack resistance Using GB / T4508 "Determination of Asphalt Ductility" as the test reference, the ductility length of the sample at 5℃ was tested. Each sample was tested 3 times, and the average value was taken. The test results were recorded in Table 1.

[0063] 3. Toughness properties Using ASTM D5801, "Standard Test Method for Toughness and Toughness of Bituminous Materials," as the testing reference, the toughness of the samples was tested. Each sample was tested three times, and the average value was taken. The test results were recorded in Table 1.

[0064] Table 1

[0065] Data Analysis: Specifically, by combining Examples 6-8 and Examples 1-3, it can be seen that the high-temperature rutting resistance, low-temperature crack resistance, and toughness of Examples 6-8 are all superior to those of Examples 1-3. The difference between Examples 6-8 and Examples 1-3 is that after the bisphenol A type epoxy resin is modified with nano-silica and nano-cellulose whiskers, on the one hand, the cured cyclobisphenol A type epoxy resin phase itself has better crack resistance, and on the other hand, a ternary chemical bonding network of "nanomaterial-epoxy resin-SBS" is formed, thereby effectively improving the high-temperature rutting resistance, low-temperature crack resistance, and toughness of asphalt.

[0066] Specifically, by combining Example 1 and Comparative Example 1, it can be seen that Example 1 has better high-temperature rutting resistance, low-temperature crack resistance, and toughness than Comparative Example 1. The difference between Example 1 and Comparative Example 1 is that the chemical cross-linking network formed by the dual-terminal epoxy group SBS and bisphenol A type epoxy resin improves the "bridging" effect of the dual-terminal SBS in the cross-linking network on the one hand, and can form the topological structure of SBS molecular chains "penetrating" the bisphenol A type epoxy resin cross-linking network on the other hand, thereby effectively improving the high-temperature rutting resistance, low-temperature crack resistance, and toughness of asphalt.

[0067] Specifically, comparing Example 1 and Comparative Example 2, it can be seen that Example 1 exhibits superior high-temperature rutting resistance, low-temperature crack resistance, and toughness compared to Comparative Example 2. The difference between Example 1 and Comparative Example 2 lies in the fact that the polar groups on the latent curing agent of the urea wall material microcapsules can form hydrogen bonds with the hydroxyl and epoxy groups on the epoxy resin molecular chain, enhancing the interfacial bonding force between the microcapsules and the epoxy resin matrix. During the curing process, after the microcapsules rupture and release the curing agent, the polyurea capsule wall fragments remain in the cross-linked network, acting as an organic rigid filler to disperse stress and toughen micro-areas, thereby effectively improving the high-temperature rutting resistance, low-temperature crack resistance, and toughness of asphalt.

[0068] Specifically, by combining Example 1 and Comparative Example 3, it can be seen that the high-temperature rutting resistance, low-temperature crack resistance, and toughness of Example 1 are all superior to those of Comparative Example 3. The difference between Example 1 and Comparative Example 3 is that the chemical cross-linking network formed by the dual-terminal epoxy group SBS and the bisphenol A type epoxy resin improves the "bridging" effect of the dual-terminal SBS in the cross-linking network on the one hand, and can form the topological structure of the SBS molecular chain "through" the bisphenol A type epoxy resin cross-linking network on the other hand, thereby effectively improving the high-temperature rutting resistance, low-temperature crack resistance, and toughness of asphalt.

[0069] Specifically, by combining Example 6 and Comparative Example 4, it can be seen that the high-temperature rutting resistance, low-temperature crack resistance, and toughness of Example 6 are all superior to those of Comparative Example 4. The difference between Example 6 and Comparative Example 4 is that the nanomaterials include nano-silica and nano-cellulose whiskers. Spherical nano-SiO2 and rod-shaped nano-cellulose whiskers are uniformly dispersed in the epoxy resin matrix by chemical bonds, forming a "sphere-rod" dual nano-synergistic reinforcement structure. The two work together to achieve a "reinforcement-toughening" dual-effect synergy of epoxy resin, thereby effectively improving the high-temperature rutting resistance, low-temperature crack resistance, and toughness of asphalt.

[0070] Specifically, by referring to Example 6 and Comparative Example 5, it can be seen that the high-temperature rutting resistance, low-temperature crack resistance, and toughness of Example 6 are all superior to those of Comparative Example 5. The difference between Example 6 and Comparative Example 4 is that the nanomaterials include nano-silica and nano-cellulose whiskers. Spherical nano-SiO2 and rod-shaped nano-cellulose whiskers are uniformly dispersed in the epoxy resin matrix by chemical bonds, forming a "sphere-rod" dual nano-synergistic reinforcement structure. The two work together to achieve the dual effect of "reinforcement-toughening" of epoxy resin, thereby effectively improving the high-temperature rutting resistance, low-temperature crack resistance, and toughness of asphalt.

[0071] The above are all preferred embodiments of this application and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.

Claims

1. A high-toughness asphalt based on SBS-epoxy graft crosslinking, characterized in that: The raw materials include the following parts by weight: 100-120 parts of base bitumen, 6-10 parts of double-terminated epoxy SBS, 2-5 parts of bisphenol A type epoxy resin, 1-3 parts of curing agent, 0.4-0.8 parts of crosslinking accelerator, 1-3 parts of compatibilizer, and 0.1-0.5 parts of stabilizer.

2. The high-toughness asphalt based on SBS-epoxy graft crosslinking according to claim 1, characterized in that: The method for preparing the di-terminated epoxy group SBS includes the following steps: S1. Under nitrogen protection, cyclohexane, styrene, and tetrahydrofuran are mixed, heated and stirred, then n-butyllithium is added. After the reaction is complete, butadiene is introduced to continue the reaction and form a polystyrene-polybutadiene diblock active chain. S2. Ethylene oxide is added to the reaction system. After the reaction is complete, epichlorohydrin is added. After the reaction is complete, a single-terminated epoxy group SBS active chain is generated. Epichlorohydrin is then added to the reaction system as a coupling agent. After the reaction is complete, a double-terminated epoxy group SBS crude product is formed. S3. The reaction was terminated by adding methanol and an antioxidant. After devolatilization, drying and granulation, the double-terminated epoxy group SBS was obtained.

3. The high-toughness asphalt based on SBS-epoxy graft crosslinking according to claim 2, characterized in that: The bisphenol A type epoxy resin is prepared by modification. The method for preparing the modified bisphenol A type epoxy resin includes the following steps: P1. Nanomaterials are added to toluene, ultrasonically dispersed, and then silane coupling agent and triethylamine are added. The reaction occurs under nitrogen protection. After the reaction is completed, the nanomaterials with surface-grafted epoxy groups are obtained by separation, washing and drying. P2. After mixing the nanomaterial with epoxy groups grafted on the surface in step P1 with bisphenol A type epoxy resin, toluene, and hydroquinone, the mixture is ultrasonically dispersed and then fully reacted under nitrogen protection. After the reaction is completed, the mixture is distilled under reduced pressure to obtain modified bisphenol A type epoxy resin.

4. The high-toughness asphalt based on SBS-epoxy graft crosslinking according to claim 3, characterized in that: The mass ratio of the nanomaterial to bisphenol A epoxy resin is (6-13):

100.

5. A high-toughness asphalt based on SBS-epoxy graft crosslinking according to claim 4, characterized in that: The nanomaterials include nano-silica and nano-cellulose whiskers, and the mass ratio of the nano-silica to the nano-cellulose whiskers is (2-5):

1.

6. The high-toughness asphalt based on SBS-epoxy graft crosslinking according to claim 3, characterized in that: The curing agent is a latent curing agent for polyurea wall material microcapsules, the core material of the latent curing agent for polyurea wall material microcapsules is triethylenetetramine, and the wall material of the latent curing agent for polyurea wall material microcapsules includes toluene diisocyanate and diethylenetriamine.

7. The high-toughness asphalt based on SBS-epoxy graft crosslinking according to claim 6, characterized in that: The preparation method of the latent curing agent for the polyurea wall material microcapsules includes the following steps: S10. Triethylenetetramine is added to ethyl acetate and stirred until homogeneous to obtain a triethylenetetramine solution. Toluene diisocyanate is then added and stirred thoroughly to obtain an oil phase. Tween-80 and diethylenetriamine are added to deionized water and stirred until homogeneous. The pH is adjusted to 8-10 with a pH adjuster to obtain an aqueous phase. S20. The oil phase is added to the aqueous phase to form an oil-in-water emulsion. Under nitrogen protection, the emulsion is allowed to react fully. After the reaction is complete, the emulsion is separated, washed, and dried to obtain a latent curing agent for polyurea wall material microcapsules.

8. The high-toughness asphalt based on SBS-epoxy graft crosslinking according to claim 7, characterized in that: The mass ratio of the core material to the wall material is 1:(0.6-0.8).

9. The high-toughness asphalt based on SBS-epoxy graft crosslinking according to claim 1, characterized in that: The crosslinking promoter is one of 2-methylimidazole, triethylamine or benzyldimethylamine, the compatibilizer is one of SBS-g-MAH or epoxidized soybean oil, and the stabilizer is one of sulfur or dicumyl peroxide.

10. A method for preparing high-toughness asphalt based on SBS-epoxy graft crosslinking as described in claim 1, comprising the following steps: S100. After heating the base asphalt, add double-ended epoxy group SBS, compatibilizer and stabilizer, stir evenly to obtain a pre-dispersion; S200: Add bisphenol A type epoxy resin and crosslinking accelerator to the pre-dispersion and stir evenly; then add curing agent, stir thoroughly, and cure to obtain high-toughness asphalt.